Influence of Supply Current to the Characteristics of Reactive Oscillating Motors - Brazaitis, A.; Guseinoviene, E. (Elektronika ir Elektrotechnika, 2011)
Two tasks were solved in this article. It is proven that partition of synchronous reactive oscillating motors to reactive oscillating motors and pulsating current ones is baseless, since some of their behavior features and working characteristics are different only because of different supply currents. It is offered to deny this partition and supply sources and drives of these motors to call alternating current drives and pulsating current drives. The second task - square of motors’ current is treated as dependent variable and called the converted current. This abstract variable allows to take a look at these motors deeper and visually. Ill. 1, bibl. 5, tabl. 3 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.111.5.370